Աշխատաժամը՝ որպես գովազդային վավերապայման թիֆլիսահայ պարբերական մամուլում - Տարոն Դանիելյան (ՀՀ ԳԱԱ հրատ.)
В рекламных текстах время и часы работы исполняют одну и ту же информационную функцию, целью которой является повышение уровня связи между рекламодателем и потребителем информации, организация и регулирование действий коммуникаторов для достижения ожидаемого результата. This article considers the time and the time-tables of working hours in advertismrents as information elements executing the same informing act. They heighten the extent of communication between the advertisers and their target audience, organize and regulate their activities as well so that the expected outcome can be achieved.
Keywords: Advertising; Journalism; The periodical Press, etc.